Association of Body Composition With Serum Cholesterol and Body Mass Index in Healthy Pakistani Adults - Ali, Ujala; Riaz, Bushra; Nadeem, Muhammad Sohaib; Alam, Amir; Khan, Muhammad Alamgir (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the association of serum cholesterol and body mass index with body composition in the healthy Pakistani adults. Study Design: Cross sectional study. Place and Duration of Study: Physiology Department, Army Medical College Rawalpindi/National University of Medical Sciences (NUMS), in collaboration with Armed Forces Institute of Rehabilitation Medicine (AFIRM) Rawalpindi and Clinical Pathology Laboratory (CPL), Pak-Emirates Military Hospital, Rawalpindi. (Duration to be asked form the authors). Methodology: The total study sample of 100 participants was taken, that comprised of two groups. Group-1 included male participants (n=50) while group-2 included female participants (n=50). The participants were healthy adults of ages 18-60 years having same physical activity background. Body composition of the participants was evaluated by bioelectric impedance analysis machine. Measurement of serum cholesterol was carried out by the Bosh Diagnostic Kit. Body Mass Index (BMI) was determined by the formula. Results: Serum cholesterol was found to be significantly correlated with body fat mass and percent body fat in males (r-value = 0.90 and 0.82, p-value <0.001 and 0.002 respectively) and in females there was significantly positive correlation with the body fat mass (r-value=0.51, p-value 0.007), skeletal muscle mass (r-value = 0.59, p-value 0.005), total body water (r-value=0.67, pvalue 0.006) and fat free mass (r-value=0.47, p-value 0.008). Conclusion: Serum cholesterol and BMI were associated with the body composition in females but with only fat parameters in the males. .